Vanadium salt inhibits osteoclast formation and preserves bone integrity in a rat model of type-1 diabetes associated bone loss - Joshua Greendyk; James Thornton; Darian Napoleon; Michael Greenberg; Anthony Lin; Mike Levidy; Jonathan R. Lopez; Maximilian Muñoz; Kevin Innella; Yazan Kadkoy; Maya Deza Culbertson; Jessica A. Cottrell; et al. (BioMetals, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Impact of an estuarine dam on sediment distribution and accumulation in the Geum Estuary, South Korea - Timothy M. Dellapenna; Guan-hong Lee; Jonathan Rogers; Peng Lin; Joshua Alarcon; Jongwi Chang (Estuarine, Coastal and Shelf Science, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Are we attending to climate change? A systematic review of the cognitive science literature - Joshua M. Carlson; Lin Fang; Mikenna Weiler; Abigail Dawson (Cognitive Processing, 2025)

Temporal impact of treated wastewater irrigation on field hydraulic conductivity and water-conducting macroporosity - Lin Wang; Tim De Cuypere; Sabien Pollet; Emmanuel Abatih; Adeyemi Joshua Olasore; Sarah Garré; Wim Cornelis (Soil and Tillage Research, 2025)

Associations between brominated and organophosphate flame retardant levels and inflammatory biomarkers in maternal blood, cord blood, and placental tissue at mid-gestation - Vince Nguyen; Neha Sehgal; Lin Li; Dana E. Goin; Rachel Morello-Frosch; Tracey J. Woodruff; Julia Varshavsky; June-Soo Park; Stephanie L. Gaw; Joshua F. Robinson; Stephanie M. Eick (Science of The Total Environment, 2025)

Exploring the nexus between transit-based job accessibility and labor market outcomes among marital immigrants - Joshua Philip Suarez; S.K. Jason Chang; Jen-Jia Lin (Journal of Transport Geography, 2025)

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Psychosocial stress and associations with inflammation in mid-gestation maternal, fetal, and placental tissue - Neha Sehgal; Lin Li; Dana E. Goin; Jessica Chen; Unurzul Jigmeddagva; Rachel Morello-Frosch; Tracey J. Woodruff; Stephanie L. Gaw; Joshua F. Robinson; Stephanie M. Eick (Reproductive Toxicology, 2025)

Long-term exposure to air pollution and esophageal cancer incidence: A large-scale prospective cohort study - Xuwei Tang; Chanchan Hu; Zhifeng Lin; Yulan Lin; Xiaoxu Xie; Weilin Chen; Jianwen Wang; Joshua Ye; Zhijian Hu; Zhi-Ying Zhan (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Polyelectrolyte nanofiltration membranes for base separation and recovery - Joshua L. Livingston; Abigail Cafferty; Riley Miller; Allison V. Cordova-Huaman; Jin Zhang; G. Kane Jennings; Shihong Lin (Water Research, 2025)

Advanced food contaminant detection through multi-source data fusion: Strategies, applications, and future perspectives - Selorm Yao-Say Solomon Adade; Hao Lin; Nana Adwoa Nkuma Johnson; Xorlali Nunekpeku; Joshua Harrington Aheto; John-Nelson Ekumah; Bridget Ama Kwadzokpui; Ernest Teye; Waqas Ahmad; Quansheng Chen (Trends in Food Science & Technology, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Estimating soil water retention curves from thermal conductivity measurements: A percolation-based effective-medium approximation - Yongwei Fu; Lin Liu; Yili Lu; Robert Horton; Tusheng Ren; Joshua Heitman (Journal of Hydrology, 2023)

GPT Technology to Help Address Longstanding Barriers to Care in Free Medical Clinics - Hannah Ong; Joshua Ong; Rebekah Cheng; Calvin Wang; Murong Lin; Dennis Ong (Annals of Biomedical Engineering, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

The spongiform tissue in Strumigenys ants contains exocrine glands - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Joshua C. Gibson; Sara McGuire; Andrew V. Suarez; Johan Billen (Arthropod Structure & Development, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Changing how you look at climate change: attention bias modification increases attention to climate change - Joshua M. Carlson; Madeline Voltz; John Foley; Lisa Gentry; Lin Fang (Climatic Change, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention - Lindsay F. Kramzer; Krystal T. Hamorsky; Phillip W. Graebing; Lin Wang; Joshua L. Fuqua; Nobuyuki Matoba; Amanda B. Lasnik; Bernard J. Moncla; Junmei Zhang; Kenneth E. Palmer; Lisa C. Rohan (AAPS PharmSciTech, 2021)

Structural analysis of glycosaminoglycans from Oviductus ranae - Haiyue Huang; Jin Mao; Quntao Liang; Jianghui Lin; Lilong Jiang; Shutao Liu; Joshua S. Sharp; Zheng Wei (Glycoconjugate Journal, 2021)

Assessment of transmission risk in WSSV‐infected shrimp Litopenaeus vannamei upon cooking - Luis Fernando Aranguren Caro; Hung N. Mai; Linda Nunan; Joshua Lin; Brenda Noble; Arun K. Dhar (Journal of Fish Diseases, 2020)
White spot syndrome virus has been a threat to the global shrimp industry since it was discovered in Taiwan in 1992. Thus, shrimp‐producing countries have launched regulations to prevent import of WSSV‐infected commodity shrimp from endemic areas. Recently, cooked shrimp that is infected with WSSV tested positive by PCR. However, there is no study to determine the infectivity of WSSV in cooked shrimp that tested positive by PCR. In the present study, WSSV‐infected shrimp were cooked at boiling temperature for different times including 0, 1, 3, 5, 10 and 30 min. Upon exposure to boiling temperature, WSSV‐infected shrimp were fed to SPF shrimp ( Litopenaeus vannamei ). The result showed experimentally challenged shrimp from 0‐min treatment (positive control) indeed got infected with WSSV. However, experimentally challenged shrimp that were fed tissues boiled at 1, 3, 5, 10 and 30 min were not infected with WSSV. Mortality data showed that only the positive control (0‐min) treatment displayed high mortality, whereas no mortality was observed in any other treatment category. These findings suggest that cooking shrimp at boiling temperature for at least 1 min might prevent any potential spread of WSSV from endemic countries to other geographical areas where WSSV has not yet been reported.

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

Physicochemical and In Vitro Evaluation of Drug Delivery of an Antibacterial Synthetic Benzophenone in Biodegradable PLGA Nanoparticles - Gabriella Costabile; Kathrin I. Gasteyer; Venkatereddy Nadithe; Katherine Van Denburgh; Qian Lin; Shiv Sharma; Joshua J. Reineke; Steven M. Firestine; Olivia M. Merkel (AAPS PharmSciTech, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Identification and molecular mapping of Rps11, a novel gene conferring resistance to Phytophthora sojae in soybean - Jieqing Ping; Joshua C. Fitzgerald; Chunbao Zhang; Feng Lin; Yonghe Bai; Dechun Wang; Rajat Aggarwal; Maqsood Rehman; Oswald Crasta; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Characterization of ammonia gas release from concrete added with ammoniated fly ash - Lin Shou; Joshua Hayes; Weizhi Cheng; Chang-Yu Wu; Timothy Townsend; Tim Vinson; John Schert (Air Quality, Atmosphere & Health, 2014)

Assessing the prospects of genome-wide association studies performed in inbred mice - Wan-Lin Su; Solveig K. Sieberts; Robert R. Kleinhanz; Karine Lux; Joshua Millstein; Cliona Molony; Eric E. Schadt (Mammalian Genome, 2010)

EMMC technology for treatment/reuse of dilute dairy wastewater - Rhoda Luo-Ting Lin; Joshua Lelemia Irvine; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2009)

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)